THE USE OF CRITICAL THINKING TECHNIQUE STUDYING A FOREIGN LANGUAGE AT A HIGHER EDUCATIONAL INSTITUTION - Надія Бреславець (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article is devoted to the theoretical analysis of skills formation and to the use of critical thinking technique when studying a foreign language at a higher educational establishment. The essence, stages and phases of critical thinking technique have been highlighted, methods of its usage have been grounded. The process of investigation has revealed that introduction of critical thinking technique skills facilitates the increase of foreign language study effectiveness, livens up the work of the students aimed at achieving their personal goals of studies, calls the teachers to rethink the essence of the updated educational process.